Efficient Data Search System for Large-Scale Mobile Wireless Networks using Secured and Centralized Routing Protocol - George, Sulu; Azeez, Arifa (IJRDO -Journal of Computer Science Engineering, 2015)
This paper particularly addresses the data searchproblem in large-scale wireless networks with high mobilityand density. Due to this, in a large scale network it isdifficult to fetch the data from the nodes into a wirelessnetwork. Because of high overhead and difficulty of datadiscovery, the nodes will fail to fetch the data flexibly fromthe nodes and they cannot give the query service as weexpect. Locality based distributed Data search system(LORD) is been used in the paper in order to overcome thisproblem. To increase the security and efficiency, we useEfficient Hybrid Routing protocol which reduces thecomplexity by minimizing the transmission time. Alsobacktracking algorithm is used for updating when one nodemoves into another region. The data will be published to aparticular zone in a large network. When a user receives ametadata query from the user node, the file will be fetcheddirectly from the particular centralized server and retrievesthe data to the user.